Zeolite protects mice from iron‐induced damage in a mouse model trial. Issue 11 (6th October 2018) - Fan, Xiyong; McLaughlin, Chris; Ravasini, Jason; Robinson, Cleo; George, Anthony M.
Abstract : For centuries, zeolites have been used for their utility in binding metals, and they feature in a multitude of agricultural and industrial applications in which the honeycombed zeolite structures form ideal ion exchangers, catalysts and binding agents. Zeolites are currently in a transition period, moving towards implementation in human ailments and diseases. Here, we postulated that zeolites may be able to counter the effects of excess iron and conducted a mouse model trial to gauge the utility of this notion. We used the transgenic mouse strain MexTAg299 for a thirty‐week pilot trial in which iron polymaltose and/or the zeolite clinoptilolite was injected into the peritoneum twice weekly. Mice were sacrificed at the end of the trial period and examined by postmortem and histology for significant physiological differences between mouse subgroups. In this study, we demonstrated that a common zeolite, clinoptilolite, is able to maintain the general health and well‐being of mice and prevent iron‐induced deleterious effects following iron overload. When zeolites are given with iron biweekly as intraperitoneal injections, mice showed far less macroscopic visual organ discoloration, along with near normal histology, under iron overload conditions when compared to mice injected with iron only. The purpose of the present pilot study was to examine potential alternatives to current iron chelation treatments, and the results indicate an advantage to using zeolites in conditions of iron excess. Zeolites may have translational potential for use in cases of human iron overload. Abstract : Zeolites are microporous minerals that are ideally suited to binding metals such as iron within their cagelike structures. We investigated whether the common zeolite clinoptilolite could counter the effects of iron overload. We injected mice in the abdominal cavity with iron and/or clinoptilolite over a period of 30 days. Iron‐treated mice showed tissue and cellular damage, whereas in the co‐injected mice, clinoptilolite was able to maintain general health and well‐being by preventing iron‐induced deleterious effects.